Cyclic behavior and hysteretic model of steel ring restrainers. (December 2021) - Sun, Jubo; Wang, Zhanfei; Zhang, Qiang; Ge, Hanbin
Abstract: Previous studies have investigated the mechanical behavior of steel ring restrainers (SRRs) under monotonic loading, while that of SRRs under cyclic loading is unclear. This study investigates the effects of configuration dimensions and steel grades on the cyclic behavior of the SRRs through an experiment and numerical simulations. An experimental study on six SRR specimens was conducted under cyclic loading. Then, numerical models were validated by the experimental results and further employed to carry out an extensive parametric analysis. A hysteretic model of the SRRs and corresponding formulae were proposed. Finally, a design procedure of the SRRs was presented. The results show that the proposed SRR has much higher deformation capacity compared with conventional restrainers such as cable restrainers and stoppers. It is also found that the envelope curve under cyclic loading is consistent with the force-displacement curve under monotonic loading. The unloading and reloading stiffnesses of the proposed SRR are low at small displacement ranges, while increasing significantly as the displacement increases. They close to the peak load decreases significantly, and a subsequent fracture occurs soon after the peak load is reached. Moreover, predictions given by the proposed hysteretic model are in good agreement with experimental and numerical results. Graphical abstract: Unlabelled Image Highlights: Cyclic tests of a newly proposed steel ring restrainer (SRR) were conducted. The envelope curve shows consistency with the load-displacement curve under monotonic loading. The hysteretic model of the SRR was proposed and matches well the experimental results. A simplified design procedure of the SRRs was proposed.